A Brainstorming Design: “Coffee Table Book as a Main Media and Other Supporting Medias for Promotion of Javanese Gamelan - Wahyu Nugroho Hari Mardiko; Mohammad Suharto; Esty Wulandari (Proceedings Series on Social Sciences & Humanities, 2023)
The awareness of most Indonesian society about the importance of Javanese gamelan culture began to fade, the tendency towards modern foreign musical instruments is increasing. Promotional strategies that are widely used in social media are still not on target due to the limitations of most rural communities in using social media. Therefore, we need an appropriate method or tool to promote the traditional Javanese Gamelan. This study used sample of several gamelan home industries in Wirun Village, Sukoharjo Regency. This study uses a descriptive qualitative research method, with literacy studies analysis and interviews following the anthropology of the target audience and comparisons of industry competitors in other regions. This study results a brainstorming design, the visual works that facilitates the sharing of information about Javanese gamelan in Wirun Village through a "coffee table book" as a main media and other supporting medias (such as logo, brosur, infographics, etc).